2005
DOI: 10.1073/pnas.0504943102
|View full text |Cite
|
Sign up to set email alerts
|

Adult mice cloned from migrating primordial germ cells

Abstract: We previously reported that the genomes of gonadal germ cells at 11.5-19.5 days postcoitum (dpc) are incompetent to support fullterm development of cloned mouse embryos. In this study, we performed nuclear transfer using primordial germ cells (PGCs) from earlier stages at 8.5-10.5 dpc. When PGC nuclei at 8.5, 9.5, and 10.5 dpc were transferred into enucleated oocytes, seven cloned embryos developed into full-term offspring. Of these, five, all derived from 8.5-or 9.5-dpc PGCs, developed into healthy adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Several polymorphisms have been described that distinguish B6 and CAST alleles of imprinted genes on chromosome 7 [27,28]. Female B6/CAST mice were mated with male Tg OG2 mice to produce (B6/CAST 3 OG2) F1 hybrid fetuses [29]. GFP-positive germ cells were collected from these F1 fetuses to perform all experiments.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…Several polymorphisms have been described that distinguish B6 and CAST alleles of imprinted genes on chromosome 7 [27,28]. Female B6/CAST mice were mated with male Tg OG2 mice to produce (B6/CAST 3 OG2) F1 hybrid fetuses [29]. GFP-positive germ cells were collected from these F1 fetuses to perform all experiments.…”
Section: Micementioning
confidence: 99%
“…One set of genomic DNA prepared from 120-200 GFP-positive germ cells was used for one PCR amplification [29]. For endogenous control and cultured female germ cells, one to two sets of genomic DNA were prepared for each stage.…”
Section: Bisulfite Genomic Sequencingmentioning
confidence: 99%
“…This epigenetic plasticity is essential to the process of germ cell sex differentiation, and the acquisition of developmental competence by both the sperm and the oocyte genomes [19]. Nuclear transfer (cloning) has been used to assess the correlation of epigenetic plasticity and developmental potential of fetal germ cell genomes [20][21][22][23][24]. We and others found that germ cell nuclei taken from fetuses at 8.5-10.5 dpc were fully competent to support development of viable cloned offspring based on inherited epigenetic programming that had not yet been erased [23,24], whereas germ cell nuclei recovered at 11.5 dpc or later were developmentally incompetent [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear transfer (cloning) has been used to assess the correlation of epigenetic plasticity and developmental potential of fetal germ cell genomes [20][21][22][23][24]. We and others found that germ cell nuclei taken from fetuses at 8.5-10.5 dpc were fully competent to support development of viable cloned offspring based on inherited epigenetic programming that had not yet been erased [23,24], whereas germ cell nuclei recovered at 11.5 dpc or later were developmentally incompetent [20][21][22]. This loss of developmental competence was correlated with the initial erasure, and subsequent biallelic resetting of genomic imprints in the germline genomes in both sexes, resulting in identical imprinting (or lack thereof) on both alleles of each imprinted gene in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is still unclear whether all the epigenetic information is reset in the germ line. However, nuclear transfer using nuclei of PGCs before the demethylation wave resulted in viable mice, whereas nuclear transfer with nuclei of demethylated PGCs resulted in embryonic lethality [19,20]. Female ES cells show global genome hypomethylation, similar to the methylation status of the inner cell mass and this is in part due to the presence of two active X chromosomes [21].…”
Section: Methylating the Dnamentioning
confidence: 99%